A Literature Review of Requirement Engineering Practices and Prioritization Techniques in Traditional and Agile Software Development - Ashish Sharma, Nikhil Govil (International Journal of Advanced Science and Technology, 2019)
Requirements Engineering (RE) is the process to identifying, understanding, maintaining & documenting the requirements of the project(s) to be developed in software engineering domain. For a legitimate RE; it is a paramount task to prioritize the requirements of the project at the initial phases of the development. Through Requirement Prioritization (RP), we can pin down which specific requirements of the software system should be included in a certain release. The main intention behind prioritizing the requirements is to shrink the associated risks during development. But as the changes in requirements are welcomed in Agile Software Development (ASD); it becomes very herculean task to prioritize the requirements. This paper systematically reviews the literatures related to RP by taking into account their strengths and weaknesses. This survey will help practitioners to better understand and finalize appropriate requirement prioritization technique as per the behavior of their project.